Cultural capital and internal migration trajectories of recently enrolled students at the Universidad Veracruzana - Suárez Domínguez, José Luis (2020)
In this article, we investigated the migratory profiles of recently enrolled university students. Migration studies have recently taken an interest in student migration due to the presence of students in highly centralized regions. Here, the objective is to analyze the form of migration of newly enrolled students who changed their place of residence to study at the Universidad Veracruzana in Mexico. Applying Bourdieu’s theory and a mixed methodology, we identify two groups of students according to their cultural capital  which shapes their academic and migratory trajectories, and defines the value they assign to university studies.